Islamisasi Ilmu Pengetahuan dan Telaah Kritis terhadap Epistemologi Barat - Rd. Mulyadhi Kartanegara (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 1999)
The fundamental difference between modern scientific theory and Islam, particularly in scope and methodology, lies in their fundamental perspectives. My hope is for modern Muslim intellectuals to realize that the modern scientific worldview is not the only universal perspective. There exist other scholarly perspectives developed by classical Muslim scholars—and indeed scholars of other religions—that could be considered as alternatives, potentially more suitable for our culturally religious atmosphere.